Stereodirecting effects of 4-O-ortho-cyanobenzyl ether on chemical glycosylation with glucopyranosyl donor - Zhang, Han (2023)
Here we report a systematic investigation on the stereodirecting effects of a 4-O-ortho-cyanobenzyl ether (oBCN) group with a glucopyranosyl donor. Experimental studies revealed that the glycosylation reactions using this donor generally show dual-stereoselectivities depending on the acceptor nucleophilicity, that is, glycosylation of weak nucleophile acceptors generally affords α-glycosides specifically while glycosylation of strong nucleophile acceptors affords β-glycosides preferentially. DFT computations suggested that strong nucleophiles preferentially attack the predominant covalent α-glycosyl triflate intermediate in an SN2-like manner, while weak nucleophiles preferentially attack the less stable and more reactive β-glycosyl triflate with H-bond mediated direction. The first and facile synthesis of a hexasaccharide repeating unit of serotype IV group B Streptococcus capsular polysaccharide demonstrated the versatile utility of glucosyl building blocks with an oBCN functionality in carbohydrate chemistry.